2015
DOI: 10.1002/eji.201545930
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution analysis of the murine MHC class II immunopeptidome

Abstract: The reliable identification of peptides bound to major histocompatibility complex (MHC) class II is fundamental for the study of the host immune response against pathogens and the pathogenesis of autoimmune conditions. Here, we describe an improved methodology combining immuno-affinity enrichment of MHC class II complexes, optimized elution conditions and quadrupole Orbitrap mass spectrometry-based characterization of the immunopeptidome. The methodology allowed the identification of over 1000 peptides with 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
5
49
0
Order By: Relevance
“…These should more closely reflect the distribution of source proteins and in vivo peptide repertoire than do the cell lines studies described above. Sofron et al reported almost 3000 I-A d binding peptides from BALB/c spleen, and a similar number of I-A b -binding peptides from C57BL/6 spleen [6]. As in the cell line studies described above, and as described previously for I-A b from murine splenocytes [11], peptides bound to MHC II in vitro derive from proteins present throughout the cell.…”
Section: Presentation Of Endogenous and Exogenous Antigensmentioning
confidence: 86%
See 1 more Smart Citation
“…These should more closely reflect the distribution of source proteins and in vivo peptide repertoire than do the cell lines studies described above. Sofron et al reported almost 3000 I-A d binding peptides from BALB/c spleen, and a similar number of I-A b -binding peptides from C57BL/6 spleen [6]. As in the cell line studies described above, and as described previously for I-A b from murine splenocytes [11], peptides bound to MHC II in vitro derive from proteins present throughout the cell.…”
Section: Presentation Of Endogenous and Exogenous Antigensmentioning
confidence: 86%
“…Bergseng et al characterized up to 7400 HLA-DQ-bound peptides from each of several EBV-transformed B-lymphoblastoid cell lines, and used these to define peptide binding motifs for three celiac disease-associated DQ allotypes [5]. Similarly Sofron et al identified over 1000 peptides from the murine A20 lymphoma line, helping to refine the I-A d motif [6]. In each of these studies, the majority of eluted peptides derived from endogenous proteins, with a substantial fraction (up to 20%) derived from exogenous proteins brought into the cell by endocytosis.…”
Section: Presentation Of Endogenous and Exogenous Antigensmentioning
confidence: 99%
“…Moreover, the unbiased search by mass spectrometry analysis enables the detection of ligands derived from post‐translational modification, which might be missed by conventional epitope prediction . Other examples are spliced peptide variants and the so far less well described MHC II immunopeptidome, although these peptides are currently also often difficult to detect by MS. In addition, so‐called ‘hot spots’ of preferential proteasomal processing and presentation within highly expressed proteins may be identified by comparison of ligandomes derived from different samples and mapping of frequently detected regions in a protein sequence .…”
Section: Strategies For Tumour Antigen Identification On Melanomamentioning
confidence: 99%
“…Recent advances in mass spectrometry have enabled large‐scale analyses of the collection of peptides naturally presented by MHC molecules in a particular cell line. These technologies have a tremendous potential as they can generate thousands of data points in a single experiment (see for instance refs ). However, since antigen‐presenting cells normally express multiple MHC isoforms, the MHC restriction of each ligand is generally not known and must be assigned, either with a predictor of binding to MHC or through unsupervised clustering .…”
Section: Discussionmentioning
confidence: 99%